Peculiarities of the attitude of 5th-8th form school girls and boys towards learning and tendencies of change of attitude - Laužikas , J.; Juška , A. (Psichologija, 1973)
The development of a positive attitude towards learning is one of the principal aims of the present-day school. Bearing in mind that any purposeful pedagogical activity in developing the positive attitude must be based on the results of measuring the actual attitude towards learning the authors present in their article data of a series of experiments made with the purpose of measuring the actual (real) attitude of our schoolchildren - (pupils of 5th to 8th forms). They stress and compare the difference in the attitude level between boys and girls, indicate some general tendencies of its changeability as pupils go from class to class. In the article the authors also ground the way of determining one’s attitude towards learning with the help of collisional situations.
Keywords: attitude towards learning; boys and girls